Chemical investigation of Allamanda Cathartica cv. "double yellow bell" - Africa, Helena del Rio 1943-
The roots of Allamanda cathartica cv. 'Double Yellow Bell' yielded the lactonic compounds plumericin and isoplumericin. The presence of ursolic acid in the leaves of the plant was also shown. The dried and powdered plant materials were extracted in a Soxhlet apparatus using successively, petroleum ether (b.p.30-60 degrees, ether chloroform and methanol. The solvent in each case was removed and the residue worked up. The petroleum ether extract of the roots afforded 0.032% of a crystalline compound, m.p.198-200 degrees. The ether and cloroform extracts of the roots yielded 0.079% of needlelike crystals, m.p.211-212 degrees. From the ether extract of the leaves, 0.035% yield of an amorphous solid, m.p.256-260 degrees was obtained. The physical data and spectroscopic evidences obtained suggested that the isolated compounds are identical to isoplumericin, plumericin and ursolic acid respectively. This was confirmed by TCL, mixed melting point, UV, IR, mass and NMR spectral comparison with authentic samples of the corresponding compounds.
Available to the General Public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1972.
Keywords: Allamanda cathartica; Yellow Bell; Botany, Medical; Plants--Chemical analysis